(untitled) - Tuszynski, J. A. (Singapore, 1990)
This book contains introductory comments concerning the definitions, the symmetry properties and the basic formulae for matrix elements of tensor operators. The main body of text consists of tables of reduced matrix elements of double tensor operators within pn, dn and fn configurations, i.e. all the principal pure configurations of the atomic and nuclear structure.
Keywords: Matrices,Symmetry (Physics),Ma trận,Symmetry (vật lý); Tables,Tables,Biểu bảng,Biểu bảng